Influence of Ceramic Waste and Cement on the Mechanical and Hydraulic Properties, and Microstructure of the Road Sub-Base Layer - Sadek Deboucha; Hocine Ziani; Abderrachid Amriou; Walid Maherzi; Walid Deboucha (The Baltic Journal of Road and Bridge Engineering)
This study examines cement and ceramic waste (CW) for the sub-base layer of roads. This innovative method can do away with the risks associated with improper disposal of industrial waste. To achieve this objective, several proportions of cement and CW were used, ranging from 1.5 to 2% and 5% to 15%, respectively. The aim of the work was to examine the influences of CW and ordinary Portland cement (OPC) on the unconfined compressive strength (UCS), permeability, consolidation, and microstructures of untreated and treated soil of road sub-base layer. The Guelph permeameter, UCS, permeability, and one- dimensional consolidation were among the laboratory and in-situ tests that were examined; the microstructures were characterised using SEM, infrared (IR), and mercury intrusion porosimetry (MIP). The findings indicated that the high permeability of the natural soil caused harm to our road soon after construction. Applying 5 to 15% CW reduced permeability by approximately 100% and settlement by around 43%. Furthermore, under wet and immersed conditions, mixing CW and OPC with soil raised UCS by approximately 182% and 20 times, respectively. This study demonstrated that by enhancing the geotechnical properties of soil, CW and OPC combined with it could be used as a road sub-base layer material.